EVALUATION OF THE CUTANEOUES LEISHMANIASIS TREATMENT IN AL-MERGHEB, LIBYA (Journal of Academic Research, 2017)
Cutaneous leishmaniasis (CL) is a parasitic disease which endemic in the Mediterranean region, including Libya, and it is considered as main public health problem. Treatment of CL now a day's become a challenge to the scientists over the world. Pentostam has clinical efficacy against CL.  Because  of the limited data on the treatments used  for CL in addition to undesirable side effects, there has been a demand for alternative therapies for CL.  The objective of this study to evaluate the efficacy of the used remedy regime to treat the CL patients in Libya.  We found that local and systemic pentostam for CL are useful and well tolerated. Combination of local pentostam and cryotherapy improve the chances that lesions will heal more rapidly. Because some of CL lesions heal spontaneously without treatment, decisions regarding additional therapy that heal lesions faster and prevent relapse must take into account. Therefore, we believe that further clinical studies should be conducted with cryotherapy in combination with other local medication